2004
DOI: 10.3386/w10650
|View full text |Cite
|
Sign up to set email alerts
|

Do a Firm's Equity Returns Reflect the Risk of Its Pension Plan?

Abstract: This paper examines the empirical question of whether systematic equity risk of U.S. firms as measured by beta from the Capital Asset Pricing Model reflects the risk of their pension plans. There are a number of reasons to suspect that it might not. Chief among them is the opaque set of accounting rules used to report pension assets, liabilities, and expenses. Pension plan assets and liabilities are off-balance sheet, and are often viewed as segregated from the rest of the firm, with its own trustees. Pension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 13 publications
1
62
0
2
Order By: Relevance
“…Jin, Merton, and Bodie (2006) further verified the informational efficiency in the capital market by showing that, besides the value of a pension surplus or deficit, pension plan risk is closely reflected in company equity risk. Coronado, Mitchell, Sharpe, and Nesbitt (2008), however, found that investors pay more attention to the face values in the financial statements and less attention to the more pertinent footnotes regarding pension assets and liabilities.…”
Section: ©2009 Cfa Institutementioning
confidence: 71%
“…Jin, Merton, and Bodie (2006) further verified the informational efficiency in the capital market by showing that, besides the value of a pension surplus or deficit, pension plan risk is closely reflected in company equity risk. Coronado, Mitchell, Sharpe, and Nesbitt (2008), however, found that investors pay more attention to the face values in the financial statements and less attention to the more pertinent footnotes regarding pension assets and liabilities.…”
Section: ©2009 Cfa Institutementioning
confidence: 71%
“…Our measures of investment risk include the percentage of total plan assets invested in the equity markets and the pension plan asset beta (Jin, Merton, and Bodie 2006). We offer evidence that government accounting standards strongly affect risk-taking behavior, as most pension plans use higher return assumptions to discount their pension liabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Pension asset beta captures the risk of a pension plan's exposure to alternative investments, including private equity, venture capital, hedge funds, and other alternative assets. It was fi rst proposed by Jin, Merton, and Bodie (2006).…”
Section: Summary Of Our Resultsmentioning
confidence: 99%